Skręcanie Prętów Cienkościennych Typu Dwuteownika o Zmiennej Wysokości Środnika - Cywiński, Z. (Engineering Transactions, 1965)
This paper is a next step on the way to elaborate a general theory of thin-walled bars of variable: open cross-sections subjected to torsion. It is based on all classic principles of the technical torsion. theory of thin-walled bars with constant cross-sections. The theory presented relates exclusively to bars of bisymmetric I-cross-section type which change by variation of flange distance. By the way of the energy-method the fundamental differential equation of the problem (3.10) is derived, the expressions for cross-section forces [warping moment B (4.3) and torsion moments Hk (3.2) and Hω (5.12)], are established and formulae for normal – (4.6) and shearing stress (5.16) are given. In conclusion, the results obtained by the presented theory are compared with those given in the paper [4].